Design, synthesis, and biological evaluation of novel berberine derivatives against phytopathogenic fungi. Issue 10 (13th July 2022) - Zhou, Yong; Yang, Cheng‐Jie; Luo, Xiong‐Fei; Li, An‐Ping; Zhang, Shao‐Yong; An, Jun‐Xia; Zhang, Zhi‐Jun; Ma, Yue; Zhang, Bao‐Qi; Liu, Ying‐Qian
Abstract: BACKGROUND: The abuse of chemical fungicides not only leads to toxic residues and resistance in plant pathogenic fungi, but also causes environmental pollution and side effects on in humans and animals. Based on the antifungal activities of berberine, seven different types of berberine derivatives (A1 –G1 ) were synthesized, and their antifungal activities against six plant pathogenic fungi were evaluated ( Rhizoctonia solani, Botrytis cinerea, Fusarium graminearum, Phytophthora capsici, Sclerotinia sclerotiorum, and Magnaporthe oryzae ). RESULTS: The results for antifungal activities in vitro showed that berberine derivative E1 displayed good antifungal activity against R. solani with a median effective concentration (EC50 ) of 1.77 μg ml −1, and berberine derivatives F1 and G1 demonstrated broad‐spectrum antifungal activities with EC50 values ranging from 4.43 to 42.23 μg ml −1 against six plant pathogenic fungi. Berberine derivatives (E2 –E29, F2 –F18, and G2 –G9 ) were further synthesized to investigate the structure–activity relationship (SAR), and compound E20 displayed significant antifungal activity against R. solani with an EC50 value of 0.065 μg ml −1 . Preliminary mechanism studies showed that E20 could cause mycelial shrinkage, cell membrane damage, mitochondrial abnormalities and the accumulation of harmful reactive oxygen species, resulting in cell death in R. solani . Moreover, in vivo experimental results showed that the protective effect of E20 was 97.31% at 5 μg ml −1, which was better than that of the positive control thifluzamide (50.13% at 5 μg ml −1 ). CONCLUSION: Berberine derivative E20 merits further development as a new drug candidate with selective and excellent antifungal activity against R. solani . © 2022 Society of Chemical Industry. Abstract : Through structural transformation of the structural skeleton of berberine, compounds F1 and G1 with broad‐spectrum antifungal activities against six plant pathogenic fungi, and compound E1 with selective activity against Rhizoctonia solani were obtained. By further modification of compound E1, compound E20 with higher selectivity and effectiveness against R. solani was synthesized for further evaluation.